Gene Expression Differences Between Young Adults Based on Trauma History and Post-traumatic Stress Disorder - Bountress, Kaitlin E.; Vladimirov, Vladimir; McMichael, Gowon; Taylor, Z. Nathan; Hardiman, Gary; Chung, Dongjun; Adams, Zachary W.; Danielson, Carla Kmett; Amstadter, Ananda B. (Frontiers in Psychiatry, 2021)
Background: The purpose of this study was to identify gene expression differences associated with posttraumatic stress disorder (PTSD) and trauma exposure (TE) in a three-group study design comprised of those with and without trauma exposure and PTSD. Methods: We conducted gene expression and gene network analyses in a sample (n=45) composed of female subjects of European Ancestry (EA) with PTSD, TE without PTSD, and controls. Results: We identified 283 genes differentially expressed between PTSD-TE groups. In an independent sample of Veterans (n=78) a small minority of these genes were also differentially expressed. We identified 7 gene network modules significantly associated with PTSD and TE (Bonferroni corrected p≤0.05), which at a false discovery rate (FDR) of q≤0.2, were significantly enriched for biological pathways involved in focal adhesion, neuroactive ligand receptor interaction and immune related processes among others. Conclusions: This study uses gene network analyses to identify significant gene modules associated with PTSD, TE, and controls. On an individual gene level, we identified a large number of differentially expressed genes between PTSD-TE groups, a minority of which were also differentially expressed in the independent sample. We also demonstrate a lack of network module preservation between PTSD and TE, suggesting that the molecular signature of PTSD and trauma are likely independent of each other. Our results provide a basis for the identification of likely disease pathways and biomarkers involved in the etiology of PTSD.